Peran Pendidikan Karakter dalam Menciptakan Sikap Peduli Lingkungan Siswa di SMP PGRI 35 Serpong - Pujilestari, Yulita; Mulyana, Ahmad Nana Mahmur; Marasabessy, Abd. Chaidir; Azzahra, Isnaini Septa; Puteri, Ajeng Helmatasya; Sari, Ayudhiya Permata; Rahmayanti, Hilda (CV. Kurnia Grup, 2024)
This socialization is motivated by the importance of shaping the character of environmental care. Environmental care character is an effort to instill a sense of care for the environment. The character of caring for the environment is needed by everyone because by protecting the environment and caring for the environment will cause the environment to feel comfortable, avoid disease and prevent environmental damage. The school environment is the foremost educational institution in developing character education. Through school, the processes of forming and developing student character are easily seen and measured. Teachers need to teach character education at school to students because not all students get character education at home, one type of character education that needs to be applied at school is the character of caring for the environment. Seeing the importance of the character of environmental care is very necessary to be instilled early on to students starting from elementary school and junior high school. Teachers play a very important role in shaping character at school because the process of student interaction at school happens a lot with teachers, teachers are figures who are digugu and imitated by students. So the purpose of this study is to examine more deeply how the role of teachers in shaping students' environmental care character, supporting and inhibiting factors for the role of teachers in shaping students' environmental care character.